Detection method of cooking-free premixed flour and rapid ductility detection instrument of cooking-free premixed flour
The insoluble index is detected by water solubility and centrifugation, and the ductility is tested by tensile force and tensile length. The problem of difficult to quickly detect the insolubleness and ductility of the pre-cooked-free powder in the prior art is solved, and a fast and accurate detection effect is achieved.
Patent Information
- Application Number
- CN202411852687.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The prior art is difficult to quickly and accurately detect the insoluble index and ductility of boil-free ready-mixed powder, which leads to difficult timely investigation of production process problems and affects the performance and quality of food.
The insoluble index is detected by water-soluble and centrifugation, and the ductility is tested by tensile force and tensile length methods. The ductility parameters are calculated by combining the tensile force peak value and tensile distance to achieve rapid detection.
This method can quickly obtain the insoluble index and ductility parameters of boil-free ready-mixed powder, simplify the detection process, reduce costs, and is suitable for rapid inspections at the grassroots level and on-site.
Smart Images

Figure CN119595462A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of pre-prepared food detection, and in particular to a detection method for no-cooking pre-mixed powder and a rapid ductility detection instrument thereof. Background Art
[0002] No-cooking premix refers to a premix made of one or more of glutinous rice flour and edible starch as the main raw materials, with or without auxiliary materials, and is crushed, mixed, sieved, and packaged. Auxiliary materials include chemically modified starch, emulsifiers, thickeners, etc. Modified starch is a starch whose natural properties are changed by physical, chemical or biological methods. Chemically modified starch includes acetylated starch, hydroxypropyl starch, cross-linked starch, etc. Different types of modified starch have different properties and starch gelatinization conditions. Different auxiliary materials and proportions will also affect the gelatinization degree of starch, and thus affect the performance, ductility and shelf life of the finished product.
[0003] In order to ensure the performance and quality of no-cooking premixes in actual applications, troubleshoot problems in a timely manner, and meet the needs of production and consumers, manufacturers usually conduct application tests on no-cooking premixes, especially the insolubility index and ductility test of such foods. Among the many existing testing methods, there is no clear testing standard. By consulting the relevant content of premixes in the existing national standards, group standards or enterprise standards, it can be seen that most of these standards are aimed at safety testing and physical and chemical indicators, and do not test the performance of the premixes themselves and the finished products. The ductility of food refers to the ability of the food to stretch or extend without breaking when force is applied, which can specifically affect key factors such as the fluidity, formability and taste of the food. Solubility is the key performance of premixes, which affects the use effect of the finished products made of premixes. Improper processing conditions or production conditions may cause starch molecules to degrade or insufficiently cross-link, forming insoluble substances. By testing the insolubility coefficient, the effectiveness and consistency of the production or processing process can be reflected to ensure whether impurities are mixed in the production feed or whether there are major problems in the production process. Therefore, the present invention provides additional information in this regard, and it is necessary to test the insolubility index and ductility of premixed powder foods that do not require cooking.
[0004] At present, the ductility test of food in the laboratory generally uses instruments such as texture analyzers, which require more complex physical and chemical testing methods, and also need to specifically proportion various reagents to cope with the test. The operation is cumbersome and complicated, and requires specialized technicians to operate, which is not conducive to the determination of a large number of samples and the use of grassroots personnel. Moreover, it is not a test tool specifically for premixed powder foods, but more for building materials and other items with stronger ductility. In addition, grassroots personnel usually use an application test method, which is to prepare a large ball of dough based on experience, and then manually pull the dough sandwiched between two iron plates according to the feeling, until the dough is pulled a certain distance apart without breaking, and will not fall off the iron plate, and then judge its viscosity, etc. It is impossible to control the influence of various variables, and it is impossible to obtain specific parameters for judgment, resulting in the missed detection of some defective products. Summary of the invention
[0005] In order to solve the problems existing in the above-mentioned prior art, one of the purposes of the present invention is to provide a method for detecting no-cooking premixed powders, which is aimed at detecting the insolubility index, water solubility and ductility of no-cooking premixed powder foods, reflecting the production process problems of the products by water solubility and centrifugation, and testing its ductility by tension and stretching length, which can quickly obtain the corresponding parameters, so that the results can be judged through reasonable comparison. The second purpose of the present invention is to provide a rapid detection instrument for the ductility of no-cooking premixed powders. When using this instrument for detection, no additional reagents are required, the operation is quick and simple, the detection time is short, the measurement results are accurate, and it is suitable for rapid detection by grassroots personnel and on-site.
[0006] The method for detecting the no-cooking premix powder of the present invention comprises the following steps:
[0007] S1. Insolubility index test: dissolve the no-cooking premix powder in water and centrifuge it in a graduated centrifuge tube, and record the volume of the resulting precipitate;
[0008] S2. Extensibility test: Mix the no-cooking premixed flour with water in proportion to form a sample, wait until the starch in the sample is completely gelatinized, knead it into a ball and place it in a beaker for later use;
[0009] S3, quantitatively take the mixed sample with a glass rod and stick it between two opposite sheets;
[0010] S4, the two sheets are attached to each other and left to stand for a period of time, and the thickness d1 and the diameter d2 of the sample after being flattened are recorded;
[0011] S5, separating the two sheets with a uniform pulling force until the sample is broken, and recording the peak pulling force F and the distance d3 when the sample is broken;
[0012] S6. Calculate the ductility parameter σ and determine whether it meets the test standards.
[0013] In one embodiment, in step S6, the ductility parameter σ is calculated as follows:
[0014]
[0015] Where m is the mass of the sample taken quantitatively.
[0016] In one of the embodiments, in step S2, the no-cooking premixed powder and water are mixed in the following manner: weigh a certain amount of the no-cooking premixed powder, add a certain amount of 100° C. boiling water, knead into a dough, and then put it into a blender and stir for 3 to 5 minutes or take out the dough and stretch it by hand until it is a smooth dough without dry powder.
[0017] In one embodiment, in step S2, the ratio of the no-cooking premix powder to water is 1:1 to 5:6.
[0018] In one embodiment, in step S3, the mass of the sample quantitatively taken is 10 g.
[0019] In one of the embodiments, in step S4, when the two sheets are attached together, it is necessary to ensure that there is no gap after the sample is flattened, and the static time is at least 5 seconds.
[0020] In one of the embodiments, in step S5, the separation process of the two sheets adopts horizontal pulling force.
[0021] In one embodiment, in step S1, the specific method of insolubility index detection is:
[0022] S11, add 500g of water to a 1000ml beaker, start the digital display electric stirrer, and adjust the position of the stirring paddle to maintain the speed at 250-300rpm;
[0023] S12, add 70g of the no-cooking premixed powder to be tested, keep the speed at 200±25rpm, and stir for 3-4 minutes;
[0024] S13. Take out 50 ml of the sample from the stirred sample using a measuring cylinder and put it into a 100 ml centrifuge tube. Stir it evenly before sampling.
[0025] S14, placing in a centrifuge and centrifuging at 4000 rpm for 5 minutes;
[0026] S15. After centrifugation, discard the supernatant and read the numbers again.
[0027] The rapid ductility detection instrument for no-cooking premixed powder of the present invention is applied to the above-mentioned detection method of no-cooking premixed powder, comprising a base, fixed plates are vertically arranged on both sides of the base, a horizontally extending positioning column is provided between the two fixed plates, and a movable plate is sleeved on the positioning column so that the movable plate can reciprocate horizontally along the positioning column; a tensile gauge is fixedly provided on the inner side of one of the fixed plates, and the other end of the tensile gauge is connected to the first thin sheet, and the movable plate is provided with a second thin sheet at a horizontal position corresponding to the first thin sheet, and a horizontal scale is also provided on the base along the direction of the positioning column.
[0028] In one embodiment, both the first sheet and the second sheet are disc-shaped structures made of metal material, and a plurality of circular scales are provided along the center of the two opposite sides of the first sheet and the second sheet.
[0029] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0030] 1. The method of the present invention is aimed at detecting the insolubility index, water solubility and ductility of the premixed powder food without cooking. It reflects the production process problems of the product by water solubility and centrifugation, and tests its ductility by tension and stretching length. The corresponding parameters can be quickly obtained, so that the results can be judged through reasonable comparison.
[0031] 2. The test uses 100℃ boiling water to mix, which can make the no-cooking premixed powder quickly form dough. Generally, 50g of no-cooking premixed powder is mixed with 50g-60g of boiling water. After testing, the ratio exceeding this ratio will make the dough not sticky and unable to form a ball, or there will be too much powder, thus forming more pores, which will affect the test effect. The sample is quantitatively taken in 10g, which can make the dough have a certain visual thickness when it is flattened, which is convenient for reference value and subsequent calculation.
[0032] 3. The instrument of the present invention has a compact structure and high precision. No additional reagents are required when using the instrument for detection. The operation is quick and easy, the detection time is short, and the measurement results are accurate. It is suitable for grassroots personnel and rapid detection on site.
[0033] 4. When using this instrument, the test dough should be placed on the first thin sheet, and the movable plate should be moved to press the first thin sheet with the second thin sheet on it. After standing for 5 seconds, the thickness and circular diameter of the flattened test dough should be measured, and then the movable plate should be pulled open slowly and evenly. With the limit cooperation of the positioning column, the movable plate should be kept vertically sliding to the base as much as possible. When the test dough is broken, the distance between the movable plate and the first thin sheet and the reading of the tensile meter should be read according to the scale on the base. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1It is a flow chart of the method for detecting the no-cooking premix powder of the present invention;
[0035] Figure 2 It is a structural schematic diagram of an instrument for rapid detection of ductility of premixed powder without cooking according to the present invention.
[0036] Explanation of the reference numerals: 1-base, 2-fixed plate, 3-positioning column, 4-movable plate, 5-tensile gauge, 6-first thin sheet, 7-second thin sheet. DETAILED DESCRIPTION
[0037] The drawings are only used for illustrative purposes and should not be construed as limitations on this patent. In order to better illustrate this embodiment, some parts of the drawings may be omitted, enlarged, or reduced, and do not represent the size of the actual product. For those skilled in the art, it is understandable that some well-known structures and their descriptions in the drawings may be omitted.
[0038] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installation" and "connection" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be directly connected or indirectly connected through an intermediate medium. It can be said that the internal connection of two components is connected. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. The technical solution of the present invention is further explained below in conjunction with the accompanying drawings and embodiments.
[0039] The inventors have found that, since the premixed powder of the non-cooking type is a special food, it is directly edible, and the manufacturer also often needs to judge the molding effect of the product application and whether its mouthfeel meets the needs of consumers through the test of its ductility, but the complicated steps and expensive cost of physical and chemical detection make it impossible for many manufacturers to do more detection, and it is difficult to ensure the quality of all products by only necessary sampling tests. And referring to the commonly used application detection method of grassroots personnel, that is, directly clamping a piece of dough with an iron plate and stretching it to both sides with hands, judging its ductility according to experience and feeling, it is more convenient and quick in actual application, but there is no control variable, and there is no clear parameter as a basis for judgment, so that sometimes a large error will be caused. In addition, because the modified starch is mostly white powder, there is no difference in appearance, and there is a risk of error in feeding, and the manufacturer also needs to test whether the premixed powder is mixed with impurities or modified starch with different properties, and there are more tests for the physical and chemical properties of the premixed powder at present, and there is less test on the accuracy of the premixed powder ingredient ratio. Therefore, the present invention further improves the method for detecting the insolubility index and ductility of premixed powder, so as to quickly detect the no-cooking premixed powder without the need for additional reagent preparation, and can derive reasonable insolubility index and ductility parameters, thereby quickly and roughly judging the production process consistency of the no-cooking premixed powder, the fluidity, formability and taste of the finished product and other key factors.
[0040] like Figure 1 As shown, the method for detecting the no-cooking premix powder of the present invention comprises the following steps:
[0041] S1. Insolubility index test: dissolve the no-cooking premixed powder in water and centrifuge it in a centrifuge tube with a scale, and record the volume of the resulting precipitate; further appearance test can be performed to observe the state, color and smell of the no-cooking premixed powder after dissolution;
[0042] S2. Extensibility test: Mix the premixed flour without cooking with water in proportion to form a sample. After the starch in the sample is completely gelatinized, knead it into a mass and place it in a beaker for later use. Starch gelatinization is a process in which starch particles absorb water, swell, rupture, and disintegrate under sufficient water conditions and lose their recognizable particle shape. Starch absorbs water, swells, and splits at high temperatures to form a uniform paste solution or dough.
[0043] S3. Use a glass rod to quantitatively take the mixed sample and stick it between two opposite sheets. The sample is generally tested at room temperature. The viscosity of the mixed sample may change differently at different temperatures. It is observed that the lower the temperature, the lower the viscosity. Cooling the sample to room temperature helps to avoid significant data errors caused by continuous temperature reduction during the measurement process.
[0044] S4, two thin sheets are attached to each other and left to stand for a period of time, and the thickness d1 and the diameter d2 of the sample after being flattened are recorded;
[0045] S5. Separate the two sheets with a uniform pulling force until the sample is broken, and record the peak pulling force F and the distance d3 when the sample is broken;
[0046] S6. Calculate the ductility parameter σ and determine whether it meets the test standards.
[0047] The method of the present invention is to detect the insolubility index, water solubility and ductility of the premixed powder food without cooking, reflect the production process problems of the product by water solubility and centrifugation, and test its ductility by tension and stretching length, and can quickly obtain the corresponding parameters, so that the results can be judged by reasonable comparison, which is simple to operate, low cost, safe and environmentally friendly, and fast to use. The method can roughly judge whether there is any error in the raw material, whether modified starch with different properties from ordinary edible starch is added or impurities of different colors are mixed by the water solubility during the insolubility index detection; and the appearance detection further judges whether impurities are mixed in the production feeding by combining the texture, smell, impurities and color during the water solubility detection; at the same time, if the premixed powder is added with anti-sticky modified starch, it can be seen from the degree of adhesion to the iron plate that the added pull-off distance will be relatively short and one of the iron plates will be smooth, which is also part of the appearance detection. In practical applications, the ductility coefficient is above a certain value or above a certain pull-off distance for an acceptable degree of starch aging. The product can first select qualified reference samples according to the standards of physical and chemical testing, and then use this method to obtain reasonable data for the reference samples, especially the calculated range of ductility parameter σ, so that when this method is used to test other products, the ductility parameter σ obtained is within the qualified range, which means that the product has good molding and excellent taste.
[0048] In step S1, the insolubility index test requires dissolving the no-cooking premix powder in water, and at this time the solubility of the solution, whether there is precipitation, whether the color is uniform, and whether there are impurities can be observed:
[0049] Color: White uniform liquid. If colorant is added to the premixed powder, the color will be evenly distributed without abnormal color. Take 20-30 ml of sample solution and place it in a beaker under natural light. Observe with the naked eye to see if the color is evenly distributed and whether there is black, gray or other abnormal colors.
[0050] Impurities: No impurities visible to normal vision; take 20-30 ml of sample solution and place it in a transparent container, place it under natural light, and observe with the naked eye whether there are abnormal precipitation or suspended matter;
[0051] Smell: No bitterness, mildew, spoilage or other peculiar smell. If there is edible starch such as cooked cake powder in the formula, there will be a special smell. If there is non-dairy creamer, there will be a milky flavor. Take 20-30ml of sample solution and place it in a clean glass beaker, and smell it directly or with a fan.
[0052] Based on the observation results, we can roughly judge whether there are any errors in the raw materials, whether modified starch with different properties from ordinary edible starch is added or impurities of different colors are mixed in. The properties of modified starch include improved frost resistance, improved elasticity, viscosity, and anti-stickiness, etc., so as to avoid possible influence on the following ductility and other tests.
[0053] The no-cooking premixed powder is generally in powder form before being processed. Therefore, in step S2, the no-cooking premixed powder needs to be mixed with water. The processing method is as follows: weigh a certain amount of the no-cooking premixed powder and add a certain amount of 100°C boiling water. After kneading into a dough, put it into a mixer and stir for 3 to 4 minutes. The time can be appropriately extended or shortened according to the amount of the sample. The high temperature of 100°C should be maintained as much as possible during the whole process, or the dough can be taken out and stretched by hand until it is a smooth dough without dry powder. The premixed powder is sampled and mixed with boiling water, mixed evenly with a mixer, or stretched and kneaded by hand for many times. The main purpose is to make the dough formed by mixing the powder and water into a smooth dough without dry powder, so as to facilitate the subsequent flattening and stretching operations. The continuous high temperature is to make the starch completely gelatinized, while reducing the influence of ungelatinized powder and air mixed in the middle on the experimental results. When there are many samples, pour the no-cook premix into a temperature-controlled mixer and stir slowly, then pour in boiling water or other high-temperature liquids, stir at high speed until the starch is completely gelatinized. During the process, try to ensure that the temperature does not drop, and then take out some dough for testing; when there are few samples, pour boiling water into a container containing no-cook premix, stir with a glass rod or silicone spatula until the liquid is no longer visible, and knead into a dough. The method with a small number of samples will have a certain error because it cannot guarantee that the temperature will not drop during kneading. If water of different temperatures is used, the degree of gelatinization of starch will be different and the viscosity of the final product will also be different. Incomplete gelatinization will accelerate the aging of the finished starch, and starch aging will cause the finished product to become hard, broken, and lose elasticity.
[0054] Specifically, in step S1, the specific method of insolubility index detection is:
[0055] S11. Add 500g of water into a 1000ml beaker. Take water at room temperature of 25°C as an example. The pH value is 6.5-7. Start the digital electric stirrer and adjust the position of the stirring paddle to ensure that it is in the water. Keep the speed at 150-200rpm.
[0056] S12, add 70g of the non-cooking premixed powder to be tested, keep the speed at 200±25rpm, and stir for 3-4 minutes; first turn on the stirrer to stir the water, and then add the powder. This way of adding powder to water can prevent the sample from absorbing water to form precipitation and gathering at the bottom and cannot be stirred by the stirring paddle. Controlling the speed can avoid uneven mixing of sample water and powder due to too low a speed, while too high a speed will cause the water and powder to stick to the edge and leave a large gap in the middle, or even splashing, affecting the results;
[0057] S13. Take out 50ml of the sample from the stirred sample with a measuring cylinder and put it into a 100ml centrifuge tube. Stir it evenly before sampling. Because some modified starches have strong water absorption and agglomeration properties, they will absorb water and agglomerate to form insoluble suspended matter.
[0058] S14, placing in a centrifuge and centrifuging at 4000 rpm for 5 minutes;
[0059] S15. After centrifugation, discard the supernatant and read the number again to prevent the supernatant from merging with the precipitate again.
[0060] In the insolubility index test, when the powder-water ratio is 1:1, the powder lumps and the result cannot be measured; when the powder-water ratio is 1:20, that is, 25g powder and 500g water, the precipitated particles after centrifugation are more dispersed, and the volume measurement error is large. Therefore, the optimal choice is a powder-water ratio of 1:7. In addition, when the agitator speed is too low, for example, 50±25rpm, the dissolution efficiency is low; when the speed is too high, such as 375±25rpm, the water powder will splash on the wall of the cup and will not fall off, and the powder attached to the stirring paddle will form lumps and cannot contact with water, affecting the results. Therefore, the preferred speed is 200±25rpm, and stirring is for 3 to 4 minutes.
[0061] In addition, in the insoluble index test, taking the white oil ice skin premix as an example, if the centrifugal speed is too low, the precipitation will be incomplete and it will be easy to re-blend with water. If the centrifugal time is too long, it will cause damage to the machine. If the centrifugal time is too short, the precipitation is not obvious and it is not convenient to read. Therefore, after many comparative experiments with controlled variables, it is known that the centrifuge is optimal for centrifugation at 4000rpm for 5 minutes. The results of multiple samplings are consistent. Centrifugation for more than 5 minutes does not affect the results. However, when centrifuged for 1 minute or the speed is only 1000rpm, some samples will have different precipitation results.
[0062] The following are the insolubility index test results of some no-cooking premix powders:
[0063] Table 1 shows the ingredients list and insoluble index test results of some no-cooking premix powders
[0064]
[0065]
[0066] It can be seen that some no-cooking premix powders are highly insoluble, with a sedimentation volume between 20-50ml. The results can roughly determine the natural edible starch and modified starch in the sample formula. Natural edible starches such as corn starch, potato starch, wheat starch, etc. are insoluble at room temperature or in cold water. Modified starch can clump or combine with water to form a viscous liquid. The amount of precipitation of no-cooking premix powder is not only related to the type of starch used, but also to the characteristics of the modified starch used, such as whether it clumps when it comes into contact with water, the strength of its water absorption, and the strength of its solubility. Taking the snow meiniang premix powder as an example, after adding water and centrifuging, a homogeneous colloidal liquid is formed, and there is no separation of precipitation and water, indicating that the modified starch added to the premix powder has the characteristics of being highly agglomerated and clumping when it comes into contact with cold water. If the insolubility index of different batches of the same samples is different, too high or too low, it may mean that the production process cannot guarantee consistency or there is a problem in the production of a batch of samples, and timely adjustments are required.
[0067] Preferably, in step S2, the ratio of the no-cooking premixed powder to boiling water is 1:1 to 5:6. The use of 100°C boiling water for mixing can make the no-cooking premixed powder quickly form dough and ensure that the starch material therein is completely gelatinized. Generally, 50g of no-cooking premixed powder is taken and mixed with 50g to 60g of boiling water. The temperature, water-powder ratio and beating time are for reference only. Different types and contents of modified starch require different temperatures and moisture contents for gelatinization. After testing, under normal circumstances, the ratio exceeding the above ratio will make the dough not sticky and unable to form a ball, or there will be too much powder, thereby forming more pores and affecting the detection effect.
[0068] Furthermore, in step S3, the sample quantitatively taken is 10g, and this sample amount can make the dough still have a certain visible thickness when it is flattened, which is convenient for reference value and subsequent calculation. At the same time, this amount is small, and it is easy to control the flattening into a round shape, without wasting the test sample, and avoiding the influence of different amounts on the test. And further, in step S4, when the two slices are attached, it is necessary to ensure that there is no gap after the sample is flattened, and the static time is at least 5s. After the sample is flattened, if the powder-water ratio is unreasonable and the water temperature is not suitable, resulting in incomplete starch gelatinization and ultimately leading to product quality problems, it usually causes small particles in the finished product and forms a crack-like surface, which ultimately leads to a decrease in ductility. At this time, it is easy to mix in air to form pores, etc., which is easy to cause uneven force and premature breakage during stretching. Therefore, static observation is also to try to ensure the accuracy of the detection method, and it can also make the sample dough adhere to the slice and not fall off easily. Preferably, in step S5, the two sheets are separated by horizontal pulling force, which is stretched horizontally to both sides. The obtained peak pulling force F is the value for breaking the dough of the test sample, and there is no need to further consider the influence of gravity.
[0069] Different types of no-cooking premixes have different ingredient lists and production processes, such as no-cooking white oil snow skin premix, green rice dumpling premix, no-cooking mochi premix and frozen snow skin premix:
[0070] Ingredients of white oil-free snow skin premix: acetylated distarch adipate, hydroxypropyl distarch phosphate, wheat starch, edible starch, non-dairy creamer, trehalose.
[0071] Production process of white oil-free snow skin premix: bake wheat starch at 140-150℃ for 1 hour, sieve the raw materials, weigh the raw materials, put them into the blender for stirring, sieve the finished products and package them.
[0072] Ingredients for green rice dumpling premix: hydroxypropyl distarch phosphate, powdered sugar, glutinous rice flour, barley grass powder, guar gum, non-dairy creamer, and glucose.
[0073] Production process of Qingtuan premix: bake glutinous rice flour at 140-150℃ for 1 hour, break white sugar granules, sieve the raw materials, weigh the raw materials, premix hydroxypropyl distarch phosphate and guar gum, put them into a blender for stirring, sieve the finished product and package it.
[0074] Ingredients for no-cooking stretched mochi premix: hydroxypropyl starch, edible starch, glucose powder, trehalose, rice flour, and skimmed milk powder.
[0075] The production process of no-cooking drawn mochi premix powder: sieving the raw materials, weighing the raw materials, putting them into the blender for mixing, sieving the finished products, and packaging.
[0076] Ingredients of frozen snow skin mooncake premix: hydroxypropyl starch, hydroxypropyl distarch phosphate, powdered sugar, glucose, non-dairy creamer, monoglyceride, calcium stearoyl lactylate.
[0077] Production process of frozen snow skin moon cake premix: crush white sugar granules, sieve the raw materials, weigh the raw materials, put them into the blender for mixing, sieve the finished product and package it.
[0078] Example 1
[0079] Taking white oil snow skin moon cake premix, green rice dumpling premix, no-cooking mochi premix and wagashi premix as examples, the method of the present invention found in a specific experiment that the tension before the sample was pulled apart was on the rise, the sample was pulled apart after reaching the peak value, and then the tension was on the decline until the sample was broken. The maximum diameter of the test sheet is 10cm, and the area beyond this cannot be tested. The samples must be cooled to room temperature during the test.
[0080] First, take 50g of premixed powder and 50g of 100℃ boiling water and mix them. Stir with a mixer and keep the temperature at 100℃ for 3 to 5 minutes. During this period of time, the premixed powder can fully absorb water, so that the sample reaches the ideal viscosity and humidity, and at the same time, the sample can begin to form gluten tissue, which is the key to giving the premixed powder sample elasticity and ductility. After kneading into a ball, place it in a beaker for later use; wait for it to cool to room temperature, use a glass rod to take 5g of the mixed sample and stick it between two relative thin slices; the two thin slices are pressed against each other to flatten the sample, and it is necessary to ensure that there is no gap after the sample is flattened. Let it stand for 5s, and record the thickness d1 and diameter d2 of the sample after being flattened; separate the two thin slices with a uniform horizontal tensile force until the sample is broken, and record the peak tensile force F and the distance d3 when the sample is broken; calculate the ductility parameter:
[0081]
[0082] Afterwards, wash the used items, and use the glass rod to take 10g and 20g of the mixed sample in the beaker again. Repeat the above steps to conduct experiments with different grams and record the corresponding data.
[0083] The test data of the premixed powder for white oil-free snowy mooncakes is as follows:
[0084] Table 2 is a data table of the mixture ratio of 50g premixed powder and 50g water for premixed powder without white oil.
[0085]
[0086] The test data of Qingtuan premix powder is as follows:
[0087] Table 3 is a data table of the mixing ratio of 50g premixed powder and 50g water for Qingtuan premixed powder
[0088]
[0089] The test data of the drawn mochi premix is as follows:
[0090] Table 4 is a data table of the mixing ratio of 50g premixed powder and 50g water for the non-cooked drawn mochi premixed powder
[0091]
[0092]
[0093] The test data of wagashi premix powder is as follows:
[0094] Table 5 is a data table of the mixed ratio of 50g premixed powder and 50g water.
[0095]
[0096] From the comparison of the above tables, it can be seen that the data of the white oil-free snowy mooncake premix, green rice dumpling premix and drawn mochi premix samples are more accurate when the weight quantitative data is 10g or 20g. In order to save the dosage and obtain more moderate data, it is the best choice to quantitatively take 10g of the test sample. This method can also quickly obtain the value of the ductility parameter σ on site to compare the ductility and taste of the tested premix.
[0097] Example 2
[0098] The difference from Example 1 is that in the first step, a standby sample is prepared by mixing 50g of premixed powder and 60g of 100°C boiling water. The other experimental steps are basically the same, and 5g, 10g, and 20g of quantitative test samples are also selected for subsequent testing. The test data of the white oil-free snowy mooncake premix powder tested by the method of this embodiment are as follows:
[0099] Table 6 is a data table of the mixing ratio of 50g premixed powder and 60g water for white oil-free snowy mooncake premixed powder
[0100]
[0101] The test data of Qingtuan premix powder is as follows:
[0102] Table 7 is a data table of the mixing ratio of 50g premixed powder and 60g water for Qingtuan premixed powder
[0103]
[0104] The test data of the drawn mochi premix is as follows:
[0105] Table 8 is a data table of the mixing ratio of 50g premixed powder and 60g water for the non-cooked drawn mochi premixed powder
[0106]
[0107] The test data of wagashi premix powder is as follows:
[0108] Table 9 is a data table of the mixed ratio of 50g premixed powder and 60g water for wagashi premixed powder
[0109]
[0110] From the comparison of the above tables, it can be seen that the test sample also needs to be quantified at 10g to easily obtain the corresponding ductility parameters, especially for the no-cooking mochi premix. Taking 20g will make the diameter after flattening exceed 10cm, which is not convenient for measuring the ductility parameters. When the test sample is small, the tensile peak F is prone to be unstable, such as the qingtuan premix. Combined with the distance d3 when it is pulled apart, the difference is large. It should be that the amount taken just crosses the critical value of the dough viscosity, affecting the dough's stickiness to the slices and its own fluidity, thus causing experimental errors. Therefore, it is also best to use a 10g qingtuan premix test sample.
[0111] In summary, this embodiment 2 is used as a comparative example of embodiment 1. It can be seen that the powder-water ratio of embodiment 1 is easier to measure the corresponding data within the detectable range for products similar to the premixed powder for white oil-free snowy mooncakes, while the powder-water ratio of embodiment 1 is required for products similar to the premixed powder for green rice balls to have better toughness and avoid the situation of no breaking distance d3. At the same time, through experiments with other different powder-water ratios, it can be seen that, for example, the premixed powder for Japanese fruit with a mixing ratio of 50g premixed powder and 40g water cannot measure data and has no viscosity. Therefore, if the powder-water ratio exceeds the above two embodiments, it is easy to make the dough have no viscosity and cannot form a ball.
[0112] In addition, for the appearance inspection, if modified starch is added to the premix to prevent sticking, it can be seen from the degree of adhesion to the iron plate that the tearing distance will be relatively short and one of the iron plates will be smooth.
[0113] Example 3
[0114] There will also be differences in the water solubility test between frozen and room temperature premixed powders. The difference lies in that when tested according to the second method, the results of adding water twice are different. Refer to the difference between the above-mentioned white oil-free snow skin mooncake premixed powder and frozen snow skin mooncake premixed powder. In order to extend the shelf life and shelf life of the finished product, the frozen snow skin mooncake premixed powder is a premixed powder for frozen storage. The finished product made from frozen snow skin mooncake premixed powder can be stored under frozen conditions, and the starch will not age due to long-term freezing conditions. The shelf life can reach 2-3 months, and it still maintains a certain ductility after thawing. However, the starch of the white oil-free snow skin premix will age and lose ductility after being frozen for two days.
[0115] Take white oil snow skin moon cake premix and frozen snow skin moon cake premix as examples.
[0116] Sample 1: Knead 50g boiling water and 50g white oil-free snow skin premixed flour until the dough is smooth and uniform;
[0117] Sample 2: 300g water, 30g white oil and 100g maltose syrup were boiled and mixed evenly, and 300g frozen snow skin premix was added and mixed for 5 minutes until the dough was smooth and even;
[0118] The two samples were frozen at -18°C for 24 hours and then dried at 30°C to speed up the thawing process and facilitate ductility testing.
[0119] Table 10 is a table showing the data of the white oil-free snowy mooncake premix and the frozen snowy mooncake premix after freezing.
[0120]
[0121] The two samples were refrigerated at 4°C for 24 hours and then dried at 30°C to speed up the thawing process and facilitate ductility testing.
[0122] Table 11 is the data table of the white oil-free snowy mooncake premix and the frozen snowy mooncake premix after refrigeration
[0123]
[0124] From the comparison in the above table, it can be seen that the frozen snow skin premix has stronger antifreeze properties than the white oil-free snow skin premix, so its ductility coefficient is relatively large, so the stretching distance and tension are relatively large. Refrigeration and freezing for the same time, because refrigeration accelerates starch aging faster than freezing, can relatively reflect the elongation performance of this premix, and it is easy to record the corresponding valid data. Therefore, in the process of testing the ductility of frozen snow skin mooncake premix, the best test method is to place the sample in an environment of -18℃ and freeze it for 24 hours.
[0125] Example 4
[0126] Different from Example 1 and Example 2, the ductility parameter σ is calculated as follows:
[0127]
[0128] Where m is the mass of the sample taken quantitatively.
[0129] In order to further reasonably calculate the extensibility parameter σ and further reduce the influence of the dough forming volume, stretching length and quality of the test sample, the above formula can be used for better comparison and more accurately judge the fluidity, extensibility and taste of the product. Combining the comparison of different powder-water ratios in Example 1 and Example 2, since some premixed powders are easy to exceed the maximum diameter of 10 cm after flattening when taking 20g quantitatively, therefore, in order to achieve the purpose of rapid detection, the test data of 10g quantitatively is taken for calculation. The extensibility parameter σ calculated in this embodiment is as follows:
[0130] Table 12 is a comparison table of new ductility parameters calculated based on the test data of quantitatively taking 10g of sample at different powder-water ratios in Example 1 and Example 2
[0131]
[0132] It can be seen from the comparison of the above tables that the calculation method of the ductility parameter σ in Example 4 can be used to perform a horizontal comparison of different products, thereby allowing different products to be tested at a more reasonable powder-water ratio, and providing a more reasonable powder-water ratio for the processing of subsequent products.
[0133] like Figure 2 As shown, the food ductility detection instrument of the present invention is applied to the above-mentioned food ductility rapid detection method, including a base 1, fixed plates 2 are vertically arranged on both sides of the base 1, a horizontally extending positioning column 3 is provided between the two fixed plates 2, and a movable plate 4 is sleeved on the positioning column 3, so that the movable plate 4 can reciprocate horizontally along the positioning column 3; a tensiometer 5 is fixed on the inner side of one of the fixed plates 2, and the other end of the tensiometer 5 is connected to the first thin sheet 6, and the movable plate 4 is provided with a second thin sheet 7 corresponding to the horizontal position of the first thin sheet 6, and a horizontal scale is also provided on the base 1 along the direction of the positioning column 3. The instrument of the present invention has a compact structure and high precision. No additional reagents are required when using the instrument for detection. The operation is quick and simple, the detection time is short, and the measurement results are accurate. It is suitable for grassroots personnel and rapid detection on site. Before using the instrument, the user needs to place the base 1 on a horizontal plane, clean the residues that may exist on the first thin sheet 6 and the second thin sheet 7, return the tensiometer 5 to zero, and ensure that the movable plate 4 can slide freely on the positioning column 3. In combination with the experimental steps of the above embodiment, when starting the test, the test dough is placed on the first thin sheet 6, and the movable plate 4 is moved to press the first thin sheet 6 with the second thin sheet 7 thereon. After standing for 5 seconds, the thickness and circular diameter of the flattened test dough are measured. If the dough is offset and becomes elliptical, the deviation is not large due to the small amount. It is preferred to read the position with the smallest diameter, and then slowly and evenly pull open the movable plate 4. With the limit cooperation of the positioning column 3, try to keep the movable plate 4 vertical to the base 1 and slide it. When the test dough is broken, read the distance between the movable plate 4 and the first thin sheet 6 and the reading of the dynamometer 5 according to the scale on the base 1, thereby completing the above-mentioned rapid detection method for the ductility of food.
[0134] Furthermore, the first sheet 6 and the second sheet 7 are both disc-shaped structures made of metal materials, and a plurality of circular scales are provided along the center of the first sheet 6 and the second sheet 7 on the two opposite sides. The test dough is placed as far as possible on the center of the first sheet 6. Through the above-mentioned operation of flattening the test dough, the dough can be adjusted to a position where the diameter is easy to read. Then, the data of the test dough during flattening can be quickly obtained by using the circular scale through direct observation during flattening or residual marks of the test dough. Preferably, the tensile gauge 5 is an electronic tensile gauge, which can record the maximum tensile peak value reached when the test dough is broken, avoiding errors caused by instantaneous observation. When resetting, the first sheet 6 should be located on the 0 scale line of the horizontal scale of the base 1. In this way, even if the first sheet 6 moves forward under the influence of tension, the distance when the test dough is broken can be obtained by subtracting the reading of the first sheet 6 from the reading of the second sheet 7, thereby reducing errors.
[0135] In the description of the present application, it should be understood that the directions or positional relationships indicated by directional words such as "front, back, up, down, left, right", "lateral, vertical, horizontal" and "top, bottom" are usually based on the directions or positional relationships shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise specified, these directional words do not indicate or imply that the device or element referred to must have a specific direction or be constructed and operated in a specific direction, and therefore cannot be understood as limiting the scope of protection of the present application.
[0136] In the figure, the description of the positional relationship is only for illustrative purposes and should not be understood as a limitation on this patent; obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made on the basis of the above description. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A method for detecting no-cooking premixed powder, characterized in that: The following steps are involved: S1. Insolubility index test: dissolve the no-cooking premix powder in water and centrifuge it in a graduated centrifuge tube, and record the volume of the resulting precipitate; S2. Extensibility test: Mix the no-cooking premixed flour with water in proportion to form a sample, wait until the starch in the sample is completely gelatinized, knead it into a ball and place it in a beaker for later use; S3, quantitatively take the mixed sample with a glass rod and stick it between two opposite sheets; S4, the two sheets are attached to each other and left to stand for a period of time, and the thickness d1 and the diameter d2 of the sample after being flattened are recorded; S5, separating the two sheets with a uniform pulling force until the sample is broken, and recording the peak pulling force F and the distance d3 when the sample is broken; S6. Calculate the ductility parameter σ and determine whether it meets the test standards.
2. The method for detecting the no-cooking premix powder according to claim 1, characterized in that: In step S6, the ductility parameter σ is calculated as follows: Where m is the mass of the sample taken quantitatively.
3. The method for detecting the no-cooking premixed powder according to claim 1, characterized in that: In step S2, the no-cooking premixed powder and water are mixed in the following manner: weigh a certain amount of the no-cooking premixed powder, add a certain amount of 100° C. boiling water, knead into a dough, and then put it into a mixer and stir for 3 to 5 minutes or take out the dough and stretch it by hand until it is a smooth dough without dry powder.
4. The method for detecting the no-cooking premix powder according to claim 3, characterized in that: In the step S2, the ratio of the no-cooking premix powder to water is 1:1 to 5:
6.
5. The method for detecting the no-cooking premix powder according to claim 1, characterized in that: In step S3, the mass of the sample quantitatively taken is 10 g.
6. The method for detecting no-cooking premixed powder according to claim 1, characterized in that: In step S4, when the two sheets are attached together, it is necessary to ensure that there is no gap after the sample is flattened, and the static time is at least 5 seconds.
7. The method for detecting no-cooking premixed powder according to claim 1, characterized in that: In step S5, the separation process of the two sheets adopts horizontal pulling force.
8. The method for detecting no-cooking premixed powder according to claim 1, characterized in that: In step S1, the specific method of insolubility index detection is: S11, add 500g of water to a 1000ml beaker, start the digital display electric stirrer, and adjust the position of the stirring paddle to maintain the speed at 150-200rpm; S12, add 70g of the no-cooking premixed powder to be tested, keep the speed at 200±25rpm, and stir for 3-4 minutes; S13. Take out 50 ml of the sample from the stirred sample using a measuring cylinder and put it into a 100 ml centrifuge tube. Stir it evenly before sampling. S14, placing in a centrifuge and centrifuging at 4000 rpm for 5 minutes; S15. After centrifugation, discard the supernatant and read the numbers again.
9. A rapid testing instrument for the ductility of premixed powder without cooking, characterized in that: A detection method for the no-cooking premixed powder as claimed in any one of claims 1 to 8, comprising a base (1), fixed plates (2) are vertically arranged on both sides of the base (1), a horizontally extending positioning column (3) is provided between the two fixed plates (2), and a movable plate (4) is sleeved on the positioning column (3), so that the movable plate (4) can reciprocate horizontally along the positioning column (3); a dynamometer (5) is fixedly provided on the inner side of one of the fixed plates (2), the other end of the dynamometer (5) is connected to a first thin sheet (6), and a second thin sheet (7) is provided on the movable plate (4) corresponding to the horizontal position of the first thin sheet (6), and a horizontal scale is also provided on the base (1) along the direction of the positioning column (3).
10. The rapid ductility detection instrument for no-cooking premixed powder according to claim 9, characterized in that: The first thin sheet (6) and the second thin sheet (7) are both circular sheet structures made of metal material, and a plurality of circular scales are provided along the center of the two opposite sides of the first thin sheet (6) and the second thin sheet (7).
Citation Information
Patent Citations
Method for measuring insolubility index of milk powder
CN106153839A
Flour dough stretching measurement apparatus
CN201194010Y
Control body amasss variable flour tensilometer
CN208254944U
Waterproof material ductility testing equipment
CN210863347U
Dough stretching measuring device
CN212780266U